EMPIRICAL ANALYSIS OF THE PERFORMANCE, RISK AND CONDITIONAL CORRELATION OF THE BRAZILIAN’S SECTORIAL INDEXES - Besarria, Cássio Nóbrega; Nóbrega, Wellington Charles Lacerda; Araújo, Breno Silva; Alves, José Neto; Almeida, Fenelon Francisco; Monteiro, Valdeir Soares; Paula, Ângelo Antonio (RACE - Revista de Administração, Contabilidade e Economia, 2016)
This paper aims to analyze both the volatility patterns and performance of the sectorial indexes of Bovespa’s main stocks and to investigate the temporal structure of the conditional correlation between these, from January 04, 2011 to November 19, 2013. The results obtained from the conditional CAPM have showed that the betas significantly vary over time and revealed an existing heterogeneity among portfolios. Regarding to volatility analysis, it perceives that volatility series of both UTIL and IEE indexes presented similar behavior and were more volatile than other indexes in the review period. The conditional correlation analysis showed that IEE and UTIL, INDX and UTIL, ICON and IMAT, IMOB and IFNC have presented a strong correlation; the construction of a portfolio of assets composed by shares of these indexes does not allow the risk diversification. Keywords: Sectorial analysis. Risk. Conditional Correlation. Análise empírica do desempenho, risco e correlação condicional de índices setoriais do Brasil Resumo O objetivo deste estudo é analisar o desempenho e os padrões de volatilidade dos índices setoriais das principais ações da Bovespa e investigar a estrutura temporal da correlação condicional entre esses, no período de 04 de janeiro de 2011 a 19 de novembro de 2013. Os resultados obtidos a partir do CAPM condicional mostraram que os betas variam significativamente ao longo do tempo e revelaram a heterogeneidade existente entre as carteiras. Em relação à análise de volatilidade, percebe-se as séries da volatilidade dos índices UTIL e IEE apresentaram comportamento semelhante e se mostraram mais voláteis que os demais índices no período analisado. Já a análise da correlação condicional mostrou que os índices IEE e UTIL, INDX e UTIL, ICON e IMAT, IMOB e IFNC apresentaram uma forte correlação e a construção de uma carteira de ativos composta por ações desses índices não permite a diversificação do risco. Palavras-chave: Análise setorial. Risco. Correlação condicional.